Competitiveness in International Trade in Knowledge-Intensive Services – The Case of Poland - Wyszkowska-Kuna, Joanna (Comparative Economic Research. Central and Eastern Europe, 2014)
The aim of this paper is to study Poland’s competitiveness in international trade in knowledge-intensive services (KIS). The author analyzes the trends in Polish KIS trade and tries to answer the question whether Poland is moving towards obtaining a comparative advantage in this field. The first part of the paper presents a definition and classification of KIS, indicators to measure competitiveness in international services trade, and a short review of the research in this field. The second part of the study is empirical. The author uses traditional indicators of international competitiveness such as: export performance, trade balance, and the RCA index. The analysis also touches upon the impact of Poland’s accession to the EU on its competitiveness in KIS trade. Finally, some possible determinants of Poland’s competitiveness in particular KIS sectors are indicated. The paper uses the Eurostat and WTO databases. The analyzed period for international transactions is usually 2000-2010, but for Poland the 1994-2010 period was used, i.e. since the European Agreement entered into force.